Bilateral Talocalcaneal and Talocalcaneocentral Luxation after a Road Traffic Accident in a Dog - Serrano-Crehuet, Tomas; Espinel-Rupérez, Jorge; Amorós, Olga; Mullins, Ronan A. (VCOT Open, 2022)
A 4-year-old, 25 kg, male, castrated, crossbreed dog was referred after having been driven over by a trailer 3 days prior. On examination, the dog was unable to ambulate on the pelvic limbs. There was crepitus, soft tissue swelling and pain on manipulation of the tarsi, with bilateral rotational and suspected mild lateral instability. Radiographs identified bilateral talocalcaneal luxation with dorsal displacement of the head of talus and bilateral avulsion fracture of lateral malleolus. A dorsomedial approach to the tarsocrural joint was performed bilaterally and the dorsal luxation of the head of talus was reduced. A 3.5 mm positional cortical screw was placed on both sides from dorsomedial head of talus to plantarolateral distal calcaneus. A temporary calcaneotibial screw was also applied bilaterally. No complications were encountered apart from mild bandage-related dermatitis, and the dog made a complete recovery. No lameness was identified on subjective gait assessment at 14 weeks and 12 months postoperatively; however, mild-to-moderate osteoarthritis affecting the talocalcaneocentral and centrodistal joints was identified at 12 months postoperatively.
Keywords: talocalcaneal luxation; talocalcaneocentral luxation; dorsal displacement of the head of the talus; dog; tarsus